Pharmacotherapeutic options for attention deficit hyperactivity disorder (ADHD) - Singh, Jarnail (International Journal of Research in Medical Sciences, 2017)
Attention deficit hyperactivity disorder (ADHD), the most common behavioral disorder in children, may disable the patient throughout life. Diagnosis of ADHD is based on DSM-IV-revised criteria. ADHD is a costly health problem and various drugs including stimulants, tricyclic antidepressants (TCAs), bupropion, pemoline, clonidine and atomoxetine have been used to treat it. Atomoxetine and stimulants are the most commonly prescribed drugs for pediatric ADHD with similar efficacy, but serious adverse events with atomoxetine have been reported.